IMPLEMENTASI PROGRAM PELAYANAN ADMINISTRASI TERPADU KECAMATAN PALU TIMUR KOTA PALU (Study Tentang Implementasi Program Pelayanan E-KTP) - Hidayat, Wahyu (Katalogis, 2017)
This research aims to analyze the Implementation of Integrated Administrasion Service Program in East Palu Distict of Palu City (A Study of e-KTP Service Program Implementation). The research used descriptive qualitative method with data collection covered observation, interview, and documentation. The informan was 5 people selected through purposive sampling. The research results reveal that the Implementation of Integrated Administration Service Program in East Palu District of Palu City (A Study of e-KTP Service Program Implementation) is not optimal yet, due to some aspects affects it, namely 1) Communication aspect is already good, 2) Resourcces aspect is not good yet, 3) Disposition aspect is not good yet too, and 4) Bureaucratic Strukture aspect is not good as well.